Cluster analysis of risk factors for chronic non-communicable diseases in elderly Brazilians: population-based cross-sectional studies in a rural town (Research, Society and Development, 2021)
Negative health behaviors incorporated into lifestyle are considered the main risk factors for chronic non-communicable diseases (NCDs) in adults and the elderly. However, the relationship between the aggregation of these factors and the sociodemographic conditions of the elderly needs to be better elucidated. The aim of this study was to analyze the simultaneity of the five risk factors for NCDs in the elderly with low economic status living in a rural city in Brazil, and their association with sociodemographic variables. Cross-sectional study was conducted with elderly people from Family Health Units of the city of Ibicui-Bahia, Brazil, where 310 elderly were enrolled. Rates of physical inactivity in leisure (PIL), alcohol consumption, sedentary behavior, overweight/obesity and tobacco consumption were collected through a questionnaire in an individual interview. The average age among participants was 71.62 (± 8.16) years. The group presenting the five behaviors had high scores in both sexes (men O/E = 242.5; women O/E = 161.7). Among men and women, the highest scores found through clustering of simultaneous NCD risk factors were for the consumption of alcohol with smoking, and physical inactivity with smoking. When analyzing the association between groups and sociodemographic characteristics, men were more physically inactive than women (OR = 0.96, CI = 0.92-0.98) and concomitantly had unhealthy habits (smoking). In conclusion, the elderly are exposed to health risk factors for concurrent CNCDs and the accumulation of these risk factors was not associated with sociodemographic variables, it is suggested that further studies be carried out with the prevalent variables as well as to analyze why the elderly population presents these levels.